Application of groundwater transport modelling in groundwater development and management: a review - Kumar Sahu, Suvendu; Mondal, Kamalesh; M, Gobinath; C.Jhariya, D. (International Journal of Advanced Geosciences, 2019)
Groundwater is one of the very sensible natural resource and to protect its quality there is need of proper management system. Groundwater modelling is very advance method for the simulation, forecasting and set remediation strategy to protect the ground-water system, it is an emerging field in groundwater study. So many scientists and researchers are working on this to prepare a groundwater management strategy and to improve the efficiency of the model. For solving the different groundwater related issues, it is important to select proper model. For the accuracy of the model result, it needs to have proper idea about the model, procedure of model run and selection of model basing on the problems. There are a smaller number of modelling software like SWAT, MODFLOW, MT3DMS, RT3D, MT3D, FLUXOS, CXTFIT, FEFLOW, Retraso-Code-Bright etc. Sometimes coupled models are also preferable as per the problem. This paper based on review of the general characteristics of different transport modelling software, methodology of the model development and its application in the different issues related to groundwater development and management.Â Â Â Â